A descriptive study of day care stapled hemorrhoidopexy surgery in grade-4 hemorrhoids under pudendal block - Arvind Kumar Shukla; Avinash Goutam; Saranshi Shrivastava; Varsha Dhakad; Meher Kalsi; Srashti Shah (Asian Journal of Medical Sciences, 2023)
Background: Hemorrhoids are one of the most common afflictions of human beings from times immemorial. It is said that 40% of population have symptoms due to hemorrhoids at some time in their lives. Stapled hemorrhoidopexy under local anesthesia has been emerging as the procedure of choice for symptomatic hemorrhoids. Aims and Objectives: The objectives of the study are as follows: (1) To assess the advantage of performing stapled hemorrhoidopexy under local pudendal block. (2) To study the post-operative complications after stapled hemorrhoidopexy. (3) To assess the feasibility of stapled hemorrhoidopexy in grade IV hemorrhoids. (4) To assess the advantages of stapled hemorrhoidopexy in anal skin regression after surgery. Materials and Methods: 50 patients of grade 4 hemorrhoids were operated by hemorrhoid stapler under local anesthesia. Results: Stapled hemorrhoidopexy under local anesthesia can be safely performed as a day care procedure in grade IV hemorrhoids. Patients following stapled hemorrhoidopexy under local anesthesia have reduced post-operative pain, hospital stay, analgesic requirements, and earlier return to work, early mobility out of bed, less operative time, short learning curve, less operative complications, cost effectiveness, and good patient satisfaction. Conclusion: Stapled hemorrhoidopexy under local anesthesia is feasible to be used in those patients who are unwilling and unfit for other modes of anesthesia with better results with lesser complication rate and as a day care procedure.